The Periodic Solutions of a Class of Difference Equations - Qi Wang; Weiling You; Gengrong Zhang (Journal of Mathematics)
In this paper, we study the periodic solutions of a class of difference equations and give a necessary and sufficient condition under which the nonnegative solutions of the equation converge to a 2k-periodic solution by using relevant theoretical knowledge such as upper and lower limits and congruence. Finally, the theoretical results are verified by numerical simulation. The method used in this paper provides an idea for the study of high periodic solutions.